Peran Pemberdayaan Kesejahteraan Keluarga (PKK) dalam Upaya Pencegahan Penyalahgunaan Wewenang - Nurhayati, Ema; Pranoto, Edi; Riyanto, M.; Arief, Eva; WL, Tyaswati (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
PKK organization, comprised of women (wives as husbands' companions), plays a strategic role in household management, including influencing the behavior of their husbands. The objective of this writing is to analyze the role of PKK members in preventing the abuse of power by husbands. A qualitative approach with a descriptive-analytic method is capable of integrating the theory of the welfare state and the concept of abuse of power in public services. The method used in this community service is a participatory method through Focus Group Discussions (FGD). The research results show that PKK has a strategic position in preventing abuse of power through four main functions: monitoring government programs at the grassroots level, empowering the community through education and socialization, mediating between the community and government, and strengthening good governance. The effectiveness of the PKK role is supported by an organizational structure that extends to the RT/RW level and a strong social network in the community. This research recommends the importance of strengthening the capacity of PKK cadres, developing an integrated reporting system, and increasing coordination with formal supervisory bodies. PKK not only plays a role in improving family welfare but also becomes a strategic partner for the government in preventing abuse of power, supporting the realization of clean governance and quality public services